2006
DOI: 10.1111/j.1540-8167.2006.00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Effects of Pulmonary Vein β‐Radiation in a Swine Model

Abstract: Intravascular beta-radiation can induce transmural necrosis and fibrosis of PV myocardial sleeves without PV stenosis and other unwanted effects, which supports a potential usefulness of this energy source in the treatment of AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…The pigs in the sham group underwent the same procedures except that the neurostimulator was not turned on during the experiment. For the pigs in the AF+ ablation group, they were treated with radiofrequency ablation in accordance with the procedures described in Perez‐Castellano . In brief, a P‐32 wire connected to a 2.5‐mm balloon catheter was utilized to provide β‐radiation to the superior wall of the right pulmonary vein (PV) trunk for 30 days.…”
Section: Methodsmentioning
confidence: 99%
“…The pigs in the sham group underwent the same procedures except that the neurostimulator was not turned on during the experiment. For the pigs in the AF+ ablation group, they were treated with radiofrequency ablation in accordance with the procedures described in Perez‐Castellano . In brief, a P‐32 wire connected to a 2.5‐mm balloon catheter was utilized to provide β‐radiation to the superior wall of the right pulmonary vein (PV) trunk for 30 days.…”
Section: Methodsmentioning
confidence: 99%
“…5 In their study using 60 Gy of a focal β-source for cardiac tissue ablation, Pérez-Castellano et al described endothelial denudiation, elastic lamina disruption, and pulmonary vein sleeve necrosis in the acute animals studied. 2 It was shown that these alterations progressed to intimal hyperplasia and matured to transmural fibrotic lesions within a follow-up of ≈90 days. …”
Section: X-ray Induced Lesions In Acute and Chronic Studiesmentioning
confidence: 99%
“…Although all studies using ionizing radiation suggest a certain time span is needed, there are considerable divergences in the findings with the exact time-course of lesion creation using ionizing radiation in myocardium remaining unknown. [2][3][4][5] Therefore, finding the accurate doses, the exact time-course of lesion generation, markers indicative for antiarrhythmic lesion creation, as well as for the long-term efficacy, are pivotal questions to be answered in chronic follow-up studies.…”
Section: End Points For Lesion Creationmentioning
confidence: 99%
“…The cardiac radiation effect of blocking electrical conduction had been shown experimentally in porcine and canine models by Guerra et al [12] and Perez-Castellano [13] using beta radiation seeds in a catheter directly applied to cardiac tissue. There is no report of such cardiac therapy using external beam for treatment of arrhythmias.…”
Section: Discussionmentioning
confidence: 99%